2018
DOI: 10.18332/tid/84864
|View full text |Cite
|
Sign up to set email alerts
|

Smoking by family members and friends and electroniccigarette use in adolescence: A systematic review and metaanalysis

Abstract: INTRODUCTION Evidence suggests that smoking by family members and friends is a strong predictor of smoking uptake in adolescents, yet the influence on electronic cigarette (e-cigarette) use has not been systematically reviewed and quantified. METHODS Relevant studies were identified by searches of the PubMed and ScienceDirect databases up to December 2016. The summary odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using a random-effects model. RESULTS A total of 21 studies were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
3
25
1
Order By: Relevance
“…The current study's findings are consistent with other cross-sectional and cohort studies [34][35][36], which have found that male gender and prior addictive substance use (including tobacco smoking) is positively associated with e-cigarette use. Other cross-sectional studies [37] have also found that smoking in the family is positively associated with student e-cigarette use, whereas the current study found that e-cigarette use in the family is a predictor of student e-cigarette use. Overall, the temporal sequence between the presumed predictors and outcomes is unclear; nevertheless, the evidence supports the idea that family members influence each other's habits with regard to the use of nicotine-containing products.…”
Section: Main Findings and Comparison With Other Studiescontrasting
confidence: 89%
“…The current study's findings are consistent with other cross-sectional and cohort studies [34][35][36], which have found that male gender and prior addictive substance use (including tobacco smoking) is positively associated with e-cigarette use. Other cross-sectional studies [37] have also found that smoking in the family is positively associated with student e-cigarette use, whereas the current study found that e-cigarette use in the family is a predictor of student e-cigarette use. Overall, the temporal sequence between the presumed predictors and outcomes is unclear; nevertheless, the evidence supports the idea that family members influence each other's habits with regard to the use of nicotine-containing products.…”
Section: Main Findings and Comparison With Other Studiescontrasting
confidence: 89%
“…They might encourage or discourage health behaviors through modeling, discussion, and advice or sharing on the health information that may help to prevent and reduce exposure to health risks. [ 12 13 25 26 ] Peers also influence teenagers’ receipt of health information (e.g., alcohol use, smoking, and sexual and deviant behaviors) and health decisions through normative peer pressures or lifestyle practices of their age group. [ 1 12 ] Therefore, youth who receive accurate information about alcohol- or smoking-related health effects might have increased health awareness and know-how to deal with the risk of using substances.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 12 ] Therefore, youth who receive accurate information about alcohol- or smoking-related health effects might have increased health awareness and know-how to deal with the risk of using substances. [ 7 14 27 ] However, vice versa , they receive inaccurate information, especially from parents or peers who drink or smoke, such as positive outcomes of alcohol use or smoking and share social network norms toward substance used;[ 13 14 28 ] youth may trust their parents or peers easily and are unable to interpret and judge the relevance of the information on risk factors. This, in turn, lead them to make decisions of trying drinking alcohol or smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the popularity and potential adverse impacts on health, an understanding of the associated factors of e-cigarettes use is warranted to further prevent adolescents from initiating e-cigarettes use. In nature, e-cigarettes are novel tobacco and nicotine products, and research has indicated that factors associated with e-cigarettes use were similar to those related to cigarette smoking [17]. From this perspective, one way to prevent e-cigarettes use in adolescents is to avoid their exposure to relevant smoking factors.…”
Section: Introductionmentioning
confidence: 99%